Impaired spatial working memory across saccades contributes to abnormal search in parietal neglect. - Husain, M; Mannan, S; Hodgson, T; Wojciulik, E; Driver, J; Kennard, C (2001)
Visual neglect of left space following right parietal damage in humans involves a lateral bias in attention, apparent in many search tasks. We hypothesized that parietal neglect may also involve a failure to remember which locations have already been examined during visual search: an impairment in retaining searched locations across saccades. Using a new paradigm, we monitored gaze during search, while simultaneously probing whether observers judged they had found a new target, or judged instead that they were re-fixating a previously examined target. A patient with left neglect following focal right parietal infarction repeatedly re-fixated right locations. Critically, he often failed to remember that these locations had already been searched, treating old targets as new discoveries at an abnormal rate. In comparison, healthy age-matched control subjects rarely re-fixated targets, and mistook old targets as new targets even more rarely. The frequency of such mistakes in the parietal patient, for different conditions, correlated with the severity of his neglect. Control experiments indicated no perceptual localization deficit in non-search tasks. These results suggest a deficit in retaining searched locations across saccades in parietal neglect, in addition to the lateral spatial bias. Moreover, the former deficit exacerbates the latter, such that patients do not realize that the rightward locations favoured by their bias have already been examined during previous fixations and, for this reason, they saccade back to them repeatedly. The combination of the two deficits (a lateral bias plus a deficit in retaining locations already searched) may thus explain the pathological pattern of search that characterizes parietal neglect: why stimuli on the right are re-examined recursively, as if being searched for the first time, and hence why stimuli on the left continue to be ignored even with unlimited viewing time. These proposals accord with recent electrophysiological and functional imaging data, demonstrating posterior parietal involvement in the retention of target locations across saccades.